Digital transformation in entrepreneurship and startups as a result of good governance - Guidji, Lakhdar (The International tax journal, 2025)
This study explores the concept of digital transformation in entrepreneurship, analysing its impact on start-ups and highlighting the opportunities and challenges faced by entrepreneurs in this context alongside the features of artificial intelligence. The study examines the necessity of digital transformation in the modern business environment, as well as its potential to promote startup growth. The research addresses the concept of digital transformation and its significance, as well as the supporting technologies, such as artificial intelligence. The research discusses how digital transformation can improve operational efficiency, reduce costs and expand market reach. It also reviews the challenges that start-ups encounter when adopting digital transformation, such as high costs, a lack of digital skills, and cybersecurity risks. Finally, the study presents strategies that can enable startups to achieve effective digital transformation.